Pengaruh Pemahaman Akuntansi Dan Skala Usaha UMKM Terhadap Kualitas Laporan Keuangan Sesuai SAK-EMKM - Ruripratiti, Ayu Carolin; Yuliati, Anik (ARBITRASE: Journal of Economics and Accounting, 2025)
This study aims to examine the relationship between company scale and the quality of financial statements of Micro, Small and Medium Enterprises (MSMEs) in Sidoarjo Regency. These reports are prepared in line with the SAK EMKM framework for MSMEs. This study adopts primary data collected from MSME participants who work in the processing sector. The results show that accounting understanding has a positive and significant effect with an original sample value of 42.8%, while financial literacy has a greater influence of 52.6% on the preparation of financial statements in accordance with SAK EMKM.These findings support the hypothesis that accounting understanding and business scale significantly affect MSME finances.